Low lipase levels as an independent marker of pancreatic cancer: a frequently neglected condition in clinical setting - Gültepe, İlhami; Başaranoğlu, Metin; Zorlu, Mehmet; Şenyiğit, Abdulhalim; Taşkale, Emine Zeynep; Zaralı, Sibel; Atay, Kadri; Köroğlu, Emine (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Low lipase levels, which may be an indication of low production due to organ failure, are frequently encountered in a clinical setting, but are usually overlooked. This study examined the values of low serum lipase levels and other clinical parameters in the diagnosis of several clinical conditions, such as in pancreatic cancer. Materials and Methods: Patients with low lipase levels (≤8 U/L) were included in this retrospective study. Clinical data, including diagnostic category, demographic properties, and biochemical and hematological measurements, including serum lipase levels, were extracted. A multivariate analysis was used to identify the independent predictors of certain diagnostic categories. Results: A total of 198 patients with low lipase levels were included. Among these patients with low lipase levels, 45 (22.7%) were diagnosed with pancreas cancer. Multivariate analysis identified low lipase level as a significant predictor of pancreas cancer (OR 0.70 [%95 CI, 0.52–0.93], p=0.02). For predicting pancreatic cancer, an optimal cut-off value of ≤5.5 U/L for lipase was utilized, which had a sensitivity and specificity of 76% and 37%, respectively. Conclusion: Low lipase levels close to zero may be an indication of pancreatic cancer and should not be underestimated in the clinical setting. However, large studies are warranted to delineate the exact diagnostic significance of such low lipase levels.